Apocalypse and Sensibility: The Role of Sympathy in Jeff Lemire’s Sweet Tooth - André Cabral de Almeida Cardoso (Transatlantica)
In Jeff Lemire’s graphic narrative Sweet Tooth, the reader is faced with a world in dissolution. The cause for world-wide disaster, a deadly disease, is a traditional element of dystopian fiction. What is more unusual about Sweet Tooth is that its protagonist seems particularly ill-suited to face the challenges that confront him in a violent post-apocalyptic world, either because he is too sensitive or because he is too vulnerable. The question Lemire raises in creating this character is whether empathy has any place in an increasingly cruel and risky world. This paper discusses the role of empathy and the related notion of sympathy in a narrative that represents it in extreme circumstances. Is sympathy to be considered as a fundamental human trait in a world in which the permanence of all human values is being threatened by violence and cruelty? or can the creation of a new species through hybridization contribute a new definition of what is human?